Viral diarrhea in structure of acute intestinal infections in children - M. U. Asilova; E. I. Musabaev; G. B Ubaydullaeva (Журнал инфектологии, 2014)
In order to evaluate contribution of the viral agents into the etiological structure of acute intestinal infection in children during the period of increase in morbidity rate due to intestinal infections from January 2009 to January 2010 there were studied 753 children with diarrheal diseases. It was shown that the diarrheal diseases have viral nature in 52,0% of cases. The Rotaviruses and adenoviruses play the leading role. The infectious agents of diarrheal diseases are presented by rotaviruses in 24,0% of cases, adenoviruses – in 19,1% of cases, astroviruses – in 8,9% of cases. The rising of sporadic morbidity with viral diarrhea was characterized by seasonality and depended on the age of children. On the basis of results of investigation for early diagnosis of viral diarrhea the introduction of the current methods of laboratory diagnosis, PCR into the work of the institutions of practical medicine may be recommended.